The Place of Information Technology in Management and Business Education 1997
DOI: 10.1007/978-0-387-35089-9_11
|View full text |Cite
|
Sign up to set email alerts
|

The whys and whats of an IT specialisation within a generalist management tertiary education

Abstract: The use ofInformation Technology (IT) in support of business is widespread and becoming more so. Indeed, it is no longer possible to meet the expectations of users of financial and other business performance information without information technology. IT both enables and supports new corporate structures and strategic thrusts. To remain competitive, companies are re-thinking how they do business and re-engineering their business processes. IT applications are being used to assist in this transition. To be able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Approximately 5% of the total credits are reserved for IT courses. Researchers such as Paturi (1997), Hewett (1997) and Shan et al (1997) believe that if students are to be prepared to meet the challenges of the contemporary business world, the credits or the IT courses offered to business students are too few and needed to be increased. The additional courses should be based on advanced digital technologies used in business, and students are urged to acquire these skills to prepare them better to understand and see the role of these technological advancement in modern business practices.…”
Section: It and Educational Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 5% of the total credits are reserved for IT courses. Researchers such as Paturi (1997), Hewett (1997) and Shan et al (1997) believe that if students are to be prepared to meet the challenges of the contemporary business world, the credits or the IT courses offered to business students are too few and needed to be increased. The additional courses should be based on advanced digital technologies used in business, and students are urged to acquire these skills to prepare them better to understand and see the role of these technological advancement in modern business practices.…”
Section: It and Educational Institutionsmentioning
confidence: 99%
“…Hewett (1997) has suggested that general business students need to take additional relevant IT units and the courses should be more application-oriented than technical.…”
Section: It and Educational Institutionsmentioning
confidence: 99%